A formal data model and object algebra for object-oriented databases - Al-Hajj, Reda; Arkun, M. Erol (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we describe a formal object-oriented data model and a corresponding object-algebra. Described in the literature are two trends in query support for object-oriented databases. The first trend is to preserve existing objects, while the other trend allows for the creation of new objects.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka